The utilization of counseling services by international students in relation to their academic and social adjustment issues - Mohd Azrin Mohd Nasir; Ainul Mardhiyah Mat Yusoff (Pusat Pengurusan & Pembangunan Mahasiswa, Universiti Kebangsaan Malaysia, 2021)
The purpose of this study was to investigate the utilization of counseling services among International Students who struggle with academic and social adjustment issue with a focus on the Republic of China and Indonesian population at one university in Malaysia. The study examined descriptive information regarding the use of counseling services and the relationship to international students’ academic and social adjustment. In addition, the statistical relationship between the academic and social adjustment of Chinese and Indonesian students and their utilization and non-utilization of counseling services was examined. The study found that the more students went to counseling services, the less academic and social adjustment issues among international students, and the better they coped with adjustment issues. Also, the results of this study indicate that friends and academic advisors were the most preferred source to get advice about adjustment issues rather than psychological helps at the university health center. This research area will be beneficial for the university in their understanding of Chinese and Indonesian student needs, responsiveness to their needs through more culturally responsive counseling services and the promotion of the use of those counseling services as a psychological help in the future.